2006
DOI: 10.1073/pnas.0606350103
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of receptor/signaling complexes in bacterial chemotaxis

Abstract: Escherichia coli chemotaxis is mediated by membrane receptor͞ histidine kinase signaling complexes. Fusing the cytoplasmic domain of the aspartate receptor, Tar, to a leucine zipper dimerization domain produces a hybrid, lzTar C, that forms soluble complexes with CheA and CheW. The three-dimensional reconstruction of these complexes was different from that anticipated based solely on structures of the isolated components. We found that analogous complexes self-assembled with a monomeric cytoplasmic domain frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
4
24
1
Order By: Relevance
“…This 1∶1 ratio was consistent with our direct measurements of binding of those proteins to chemoreceptors in conditions that form kinase-activating signaling complexes (Table 1 and Figs. 4 and 6) and several studies of kinase-activating complexes (15,21,(23)(24)(25). However, other studies have observed more CheW than CheA (16,17).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This 1∶1 ratio was consistent with our direct measurements of binding of those proteins to chemoreceptors in conditions that form kinase-activating signaling complexes (Table 1 and Figs. 4 and 6) and several studies of kinase-activating complexes (15,21,(23)(24)(25). However, other studies have observed more CheW than CheA (16,17).…”
Section: Discussionmentioning
confidence: 98%
“…For each CheA 2 there were 2.0 AE 0.2 copies of CheW, consistent with the approximately 1∶1 ratio of soluble components identified by characterization of saturable binding (Figs. 4 and 6 and Table 1) and several previous studies (15,(20)(21)(22)(23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A working architectural model for this ternary complex, based on the probable docking surfaces of each component, has been proposed [35]. Electron microscopic image analysis of particles assembled from a soluble receptor fragment, CheA and CheW also shows trimers, but with significantly altered geometry in which the three dimers are not arranged in a threefold symmetry [36,37]. The hedgerow arrangement in crystals of an archaeal receptor fragment suggests that archaeal CheA and CheW might associate with separated dimers [34].…”
Section: Architecture Of the Receptor-chea-chew Signaling Complexmentioning
confidence: 99%
“…In these overexpression strains, the receptors surprisingly form a ''zipper-like'' double layer, in which large invaginations of the inner membrane allow the cytoplasmic tips of one layer to interact with the cytoplasmic tips of a second, facing layer. This arrangement was at one point proposed to represent the activated form of the receptors (18), but its physiologic relevance was later refuted (19). Adding further complication, MCPs from Thermotoga maritima crystalized as rows of dimers (20).…”
mentioning
confidence: 99%